Transport Variability of the Irminger Sea Deep Western Boundary Current From a Mooring Array. Issue 5 (22nd May 2019) - Hopkins, J. E.; Holliday, N. P.; Rayner, D.; Houpert, L.; Le Bras, I.; Straneo, F.; Wilson, C.; Bacon, S.
Abstract: The Deep Western Boundary Current in the subpolar North Atlantic is the lower limb of the Atlantic Meridional Overturning Circulation and a key component of the global climate system. Here, a mooring array deployed at 60°N in the Irminger Sea, between 2014 and 2016, provides the longest continuous record of total Deep Western Boundary Current volume transport at this latitude. The 1.8‐year averaged transport of water denser than σ θ  = 27.8 kg/m 3 was −10.8 ± 4.9 Sv (mean ± 1 std; 1 Sv = 10 6  m 3 /s). Of this total, we find −4.1 ± 1.4 Sv within the densest layer ( σ θ  > 27.88 kg/m 3 ) that originated from the Denmark Strait Overflow. The lighter North East Atlantic Deep Water layer ( σ θ  = 27.8–27.88 kg/m 3 ) carries −6.5 ± 7.7 Sv. The variability in transport ranges between 2 and 65 days. There is a distinct shift from high to low frequency with distance from the East Greenland slope. High‐frequency fluctuations (2–8 days) close to the continental slope are likely associated with topographic Rossby waves and/or cyclonic eddies. Here, perturbations in layer thickness make a significant (20–60%) contribution to transport variability. In deeper water, toward the center of the Irminger Basin, transport variance at 55 days dominates. Our results suggest that there has been a 1.8 Sv increase in total transport since 2005–2006, but this difference can be accounted for by a range of methodological and data limitation biases. Plain Language Summary: A network of currents in the Atlantic Ocean plays an important role in the global climate system, redistributing heat, salt, nutrients, and carbon around the globe. It is made up of a northward flow of warm, salty water in the upper layers of the Atlantic, and a deep, southward flow of colder, denser water. Dense water is formed at high latitudes when surface waters release heat to the atmosphere and sink toward the seafloor. This forms the Deep Western Boundary Current that moves southward to the east of Greenland. Knowing how much water is carried and whether the current is stable is vital to our understanding of global climate. Using measurements of temperature, salinity, and current speed from instruments deployed between 2014 and 2016, we find that the Deep Western Boundary Current transports on average 10.8 × 10 6  m 3 of water a second. This transport varies in time. It increases and decreases from day to day and month to month. Eddies, waves, and other ocean currents all contribute to these fluctuations. Our results suggest that transport has increased since 2005–2006, but it is possible to account for this change by considering the limitations of previous data sets and the methods used to calculate the transport. Key Points: Volume transport of the Deep Western Boundary Current in the Irminger Sea between 2014 and 2016 was ‐10.8 +/‐ 4.9 Sv Transport variability shifts from high (2‐8 days) to low (55 days) frequencies with distance down slope No significant long‐term trend in transport was identified